2016
DOI: 10.5603/ait.a2016.0041
|View full text |Cite
|
Sign up to set email alerts
|

Changes in heart rate variability during anaesthesia induction using sevoflurane or isoflurane with nitrous oxide

Abstract: Background: The purpose of this study was to compare cardiac sympathetic and parasympathetic balance using heart rate variability (HRV) during induction of anaesthesia between sevoflurane and isoflurane in combination with nitrous oxide. Methods: 40 individuals aged from 30 to 60 years, scheduled for general anaesthesia were equally divided into sevoflurane or isoflurane groups. After 100% oxygen inhalation for a few minutes, anaesthesia was induced with nitrous oxide 3 L min -1 , oxygen 3 L min -1 and sevoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…With novel techniques for electrode manufacture and preparation described here, CNTYs are now easier to use and more reliable to implant. Anesthesia is also known to alter HRV and individual fiber dynamics [35][36][37][38][39][40][41][42][43] ; yet, vagal recordings have not been obtained under chronic conditions without anesthesia. For the first time, we have shown that vagal tone can be recorded using CNTY electrodes in awake, behaving rats, greatly expanding the scope of possible autonomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…With novel techniques for electrode manufacture and preparation described here, CNTYs are now easier to use and more reliable to implant. Anesthesia is also known to alter HRV and individual fiber dynamics [35][36][37][38][39][40][41][42][43] ; yet, vagal recordings have not been obtained under chronic conditions without anesthesia. For the first time, we have shown that vagal tone can be recorded using CNTY electrodes in awake, behaving rats, greatly expanding the scope of possible autonomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Uzun süreli düşük dozda bu ajanlara maruziyetin, ameliyathane personeline etkisi konusunda yeterli araştırmalar bulunmamaktadır. 3 Ameliyathanede sağlık çalışanlarının sürekli maruz kaldığı ve kardiyotoksisite oluşması açısından önemli olan etmenler aşağıda tartışılmıştır.…”
Section: Introductionunclassified
“…However, in practice, ECGs are recorded under a variety of conditions with one of the most common being under anesthesia. Anesthesia can complicate comparisons because it is known to affect heart rate ( Picker et al, 2001 ; Nishiyama, 2016 ) and prolong QT intervals ( Yildirim et al, 2004 ). Hence, the effects of anesthesia must be accounted for in any comparison of cardiac electrophysiology.…”
Section: Introductionmentioning
confidence: 99%